The Art of Breathing. Issue 6 (December 2016) - Anderson, Gary P.; Kotsimbos, Tom
We think in images and when we reach the limits of our seeing our imagination takes over. Medicine and visual art have been inextricably linked since antiquity. Meticulously rendered images, and detailed polychromed models, have captured and codified the human body in its magnificence and rendered its manifold decrepitudes. Physicians need to parse visual appearances with the sophistication of connoisseurs every working day. And when great medical thinkers like Paul Erlich first imagined the "antibodies" and "receptors" that now underlay the science of almost our entire therapeutic pharmacopeia, that imagining was conveyed in beautiful conceptual diagrams that still astonish in the refinement of their artistry and inductive insight. The Art of Breathing is a conceptual meditation of art juxtaposed with notions of respiration and emotional thinking http://ow.ly/i7D9305ikM1